Yesus Kristus Peagabega, Terobosan Kristologis Suku Migani, Papua - Sondegau, Kleopas (Perspektif, 2018)
The writer argues that doing Christology among the Migani people of Papua is underway. Ever since the Catholic missionaries have been among the Miganese and proclaimed Jesus Christ and his Gospel, they were reminded to their ideal figure named Peagabega. Peagabega was an ideal, storico-mythical figure for the Miganese , whose life reflects some similarities to Jesus’ life and preaching, who was so close and identified himself to the powerless and the very least in the society. The Miganese found out that the life story of Peagabega, retold from generation to generation, has helped them much in holding on steadfastly to Jesus Christ, the culmination of the divine revelation and the source of Christian faith. The Catholics of Bilogai Parish in the Diocese of Timika, Papua, always use the figure of Peagabega in celebrating the Good Friday. People are impressed by such inculturated celebration which makes them more rooted in their own religious culture as well as in the Catholic faith.